Gender Equality Barriers among Maritime Students: Basis for Gender and Development Program - Sotes, Alexander; Agad, Orzon; Undap, Rodulfo; Achicoso, Jumarey; Guiral, Jasper John; Ignacio, Miles Humphrey; Gerald, Renz; Malaki, Peter; Torralba, Abran Kent (JPAIR Multidisciplinary Research, 2024)
This study investigates the gender equality barriers among maritime students in the Philippines, focusing on the influence of ethnicity and age on perceptions of these barriers. Utilizing a descriptive correlational method, the research involved 554 student respondents from the Merchant Marine Academy of Caraga, Inc. (MMACI). The study employed a questionnaire adapted from Fidan et al. (2020) to assess perceptions of structural and social barriers. The findings reveal significant gender disparities in the maritime education sector, with males dominating both BS Marine Engineering (BSMarE) and BS Marine Transportation (BSMT) programs. The study also highlights the interconnected nature of structural and social barriers, emphasizing the need for comprehensive interventions to promote inclusivity and equity. Additionally, the research identifies variations in perceptions of gender equality barriers based on ethnicity, particularly among BSMarE students. The study concludes by proposing an action plan to promote gender and development programs in the College of Maritime Education, emphasizing awareness, policy revisions, training, mentorship, and industry collaboration.
Keywords: Feminist Theory; gender development; structural barriers; family position Social barriers; gender equality; age; gender; ethnicity; descriptive-quantitative; policy development; Philippines